Survei Kemampuan Renang Gaya Dada 30 Meter Pada Mahasiswa Olahraga Angkatan 2020 STKIP Kie Raha Kota Ternate - Rifaid Saiman; Rifan Ngaji (Peneliti.net, 2022)
This study aims to determine the level of ability in swimming the 30-meter breaststroke in sports students class of 2020 at STKIP Kie Raha, Ternate City. This research is a quantitative research with a survey approach. The sample in this study were 2020 STKIP Kie Raha Sports students, Ternate City, totaling 21 students. The results showed that: in the category